YOGA CHANDRA TRADISI WATUKARU - Ni Made Adnyani (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
For a Sanatani, to understand the symbolic manifestation of Lord Śiva and his attributes, which is crowned with a crescent moon called Ardha Chandra. This crescent moon has the meaning that a devotee must develop the qualities of the heart which are the crown of a human being. The crown of man lies in his character. Having the character of the moon helps humans achieve happiness (Jagadhita). The development of the Soma (Chandra) element in the body can be obtained by practicing Asana, Pranayama and Mudra. The aims are to know the types of Yoga Chandra in the Watukaru tradition; 2) to know the benefits of Yoga Chandra in the Watukaru tradition. Efforts to achieve research objectives, used a qualitative descriptive The data analysis process is the Miles and Huberman model. Data analysis activities are data reduction, data display, and conclusion/verification. The results showed that there were 4 types of Candra Yoga, namely Chandranamaskara, Chandra Lomawati, Chandra Kirana and Chandra Kumari. Chandranamaskara yoga is a tribute to the moon as the aspect that represents gentleness. Yoga Chandra Lomawati means worship of Chandra who is in a state of injury to the Moon. Yoga Chandra Kirana is worship of the Moon in its bright, perfect light. Yoga Chandra Kumari is worship of the Moon in its crescent form. These four types of yoga chandra have their own uniqueness. Their purpose and symbolic meaning also differ from each other. But all of this chandra yoga has physical and non-physical benefits.